Investigation of CuO/mesoporous SBA-15 sorbents for hot gas desulfurization - Karvan, Oğuz; Atakül, Hüsnü (Elsevier BV, 2008)
Abstract Metal oxides, are widely used as sorbents to remove H 2 S from hot gases produced by gasification processes. These oxides, however, suffer from several problems such as low capacity, sintering, evaporation, low duration and mechanical strength. Pure metal oxides or their admixtures loaded on inert materials have been used to overcome these problems. In this study, Cu/SBA-15 type sorbents were prepared by the wet impregnation method, in which copper and SBA-15 are active and support material, respectively. The prepared sorbent samples contained 21.97% and 40.2% Cu by weight. The H 2 S removal characteristics of the samples were investigated by using a laboratory scale fixed bed reactor through sulfidation–regeneration cycles in the temperature range of 788–838 K. Characterization results showed that the preparation method does not have a serious destructive effect on the structure of the support material. The average breakthrough point sulfur uptake capacities of the sorbents with 21.97% Cu and 40.22% Cu were determined to be 0.63 and 1.57 g S/100 g adsorbent, respectively, after three cycles. The XRD and nitrogen adsorption analysis indicated that the structures of the sorbents were destructed to some extent during the sulfidation–regeneration cycles. Changes in the sulfur up take, however, were not comparable and remained limited.